PENGARUH REKENING DORMANT DAN DIGITAL MARKETING TERHADAP MINAT MENABUNG KEMBALI DENGAN MEDIASI KEPERCAYAAN NASABAH (Studi Pada Nasabah PT. Bank Negara Indonesia (Persero) Tbk, Cabang Pati) - Suluh Wisnu Hapsoro; I Made Sukresna (ITB AAS INDONESIA, 2023)
The increasingly fierce business competition, especially in the banking world today, makes banks continue to develop and create innovative products in technology to make it easier for customers. Bank BNI is a government-owned banking company that always strives to improve service quality to meet customer needs, especially in the use of internet banking, one of which is at the Pati branch office. However, this method has not been effective because there are still complaints from customers regarding the quality of services provided by the bank. Complaints from customers have an impact on the decrease in the number of transactions and the use of the account which results in the account being inactive or called a dormant account. The population in this study were customers of BNI Branch Pati with a sample of 157 respondents. Sampling using proportional random sampling method and using Structural Equation Modeling (SEM) analysis tools. Based on the results of the analysis proves that dormant accounts have a significant negative effect on customer trust so that high dormant accounts will reduce customer trust. Furthermore, good digital marketing from BNI KC Pati will increase the level of customer trust. This research also proves that good digital marketing from BNI KC Pati will increase interest in saving again. Research also proves that the higher the trust of BNI KC Pati customers, the higher the interest in saving again.